PENGARUH CAR, NPL, LDR, NIM DAN BOPO TERHADAP KINERJA KEUANGAN DENGAN GCG SEBAGAI VARIABEL MODERASI - Muhsin N Bailusy; Fadli Ali Taslim (Jurnal Manajemen Sinergi, 2020)
This study aims to determine and analyze the Effect of CAR, NPL, LDR, NIM and BOPO on Financial Performance with GCG as a moderating variable in Banking companies listed on the Indonesia Stock Exchange in 2012-2017. The sample in this study used a purposive sampling method. Based on the results of the sample selection in accordance with the criteria that have been made, then as many as 16 company samples can be chosen or as many as 45 units of observation within a period of 6 years. There are two analytical methods used in this study, namely multiple regression analysis and moderated regression analysis.The results of this study indicate that NPL affects financial performance. And CAR, LDR, NIM and BOPO variables have no effect on financial performance and good corporate governance is not able to moderate CAR, NPL, LDR, NIM and BOPO on financial performance